Ecosystem respiration increases with biofilm growth and bed forms: Flume measurements with resazurin. Issue 12 (16th December 2014) - Haggerty, Roy; Ribot, Miquel; Singer, Gabriel A.; Martí, Eugènia; Argerich, Alba; Agell, Gemma; Battin, Tom J.
Abstract In a set of streamside mesocosms, stream ecosystem respiration (ER) increased with biofilm biomass and flow heterogeneity (turbulence) generated by impermeable bed forms, even though those bed forms had no hyporheic exchange. Two streamside flumes with gravel beds (single layer of gravel) were operated in parallel. The first flume had no bed forms, and the second flume had 10 cm high dune‐shaped bed forms with a wavelength of 1.0 m. Ecosystem respiration was measured via resazurin reduction to resorufin in each flume at three different biomass stages during biofilm growth. Results support the hypothesis that ER increases with flow heterogeneity generated by bed forms across all biofilm biomass stages. For the same biofilm biomass, ER was up to 1.9 times larger for a flume with 10 cm high impermeable bed forms than for a flume without the bed forms. Further, the amount of increase in ER associated with impermeable bed forms was itself increased as biofilms grew. Regardless of bed forms, biofilms increased transient storage by a factor of approximately 4.